2018
DOI: 10.1108/et-04-2017-0050
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing career choice of tertiary students in Ghana

Abstract: Purpose -The purpose of this paper is to investigate the factors that influence Ghanaian tertiary students' career choices. The paper explores the dimensionality of the career choice factors within the Ghanaian context and also ascertains their degree of influence on students' career choices. Design/methodology/approach -The study employs survey method of research and a set of questionnaire was used to examine the factors that influence students' career choices. A total of 354 undergraduate students from the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This finding is in line with some prior studies conducted by Looi et al (2015); Denanyoh et al (2015), which remarked that family involvement is a factor that can influence a person's entrepreneurial interest. Family circumstances can affect a person's career, including their children's opportunity to be an entrepreneur in the future (Owusu et al, 2018). This study also confirmed that parents who have their businesses tend to have a great intention of being entrepreneurs for their children.…”
Section: Discussionsupporting
confidence: 71%
“…This finding is in line with some prior studies conducted by Looi et al (2015); Denanyoh et al (2015), which remarked that family involvement is a factor that can influence a person's entrepreneurial interest. Family circumstances can affect a person's career, including their children's opportunity to be an entrepreneur in the future (Owusu et al, 2018). This study also confirmed that parents who have their businesses tend to have a great intention of being entrepreneurs for their children.…”
Section: Discussionsupporting
confidence: 71%
“…Subjective norms are based on normative beliefs. Meanwhile, normative beliefs are one's belief to behave which is influenced by the hope of important people surrounding (Owusu et al , 2018). The people who are considered important are family and close friend who is capable to influence individual behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Owusu et al (2018) determined that professionals or practitioners generally had the most significant effect. Sugahara and Boland (2006) and Suryani et al (2018) identified teachers or educators to be the most influential.…”
Section: Resultsmentioning
confidence: 99%
“…Each individual has a different attitude depending on the influence that forms their behaviors. Based on TPB, the attitude towards a behavior can form an individual's attitude (Owusu, Essel-Anderson, Ossei Kwakye, Bekoe, & Ofori, 2018). The positive belief and attitude fuel the intent to grow current knowledge.…”
Section: Introductionmentioning
confidence: 99%